HARVEST AND POST-HARVEST TECHNOLOGY INNOVATIONS TO REDUCE YIELD LOSSES IN ITALY - Kim Il sun; Pak Yong Hwa Hwa; Choi Sun Hui (Techno Agriculturae Studium of Research, 2025)
The loss of agricultural produce during the harvest and post-harvest process is a significant problem facing the agricultural sector in Italy. This study aims to evaluate the effectiveness of technological innovations in reducing crop losses in crops such as grapes, olives, and wheat. This research method uses an experimental approach by comparing farmer groups that use modern harvesting and post-harvest technology with groups that use conventional methods. The results of the study show that innovative technology is able to reduce yield loss by up to 25%, improve product quality, and reduce operational costs. The conclusions of this study confirm that advanced harvesting machine technology and storage systems can be a sustainable solution to address agricultural yield loss in Italy, although more research is needed to understand the long-term impact of the adoption of these technologies.